The Kishinev Ghetto, 1941-1942: a documentary history of the Holocaust in Romania's contested borderlands - Shapiro, Paul A. ca. 20./21. Jh. (The Univ. of Alabama Press, 2015)
"The Kishinev Ghetto, 1941-1942 offers a wealth of primary sources and insightful commentary about the little-known slaughter of Jewish residents of Kishinev (Chisinau) under the military occupation of Romania by Marshal Ion Antonescu, a Hitler ally"--